2012
DOI: 10.1097/tp.0b013e318240e9b9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preexistent Hypertension on Blood Pressure and Residual Renal Function After Donor Nephrectomy

Abstract: In summary, hypertensive living kidney donors have similar outcome in terms of blood pressure and renal function as control donors, early and 1 and 5 years after donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
21
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 20 publications
7
21
1
Order By: Relevance
“…Bugge et al studied eight donors over the immediate 24 h post-nephrectomy [25]; GFR and eRPF increased by 70 % within 1 h and was maintained over 24 h. Pabico et al reported mean post-nephrectomy GFR increase of 37 % and mean eRPF of 55 %; the FF was not significantly different pre-and post-nephrectomy [26], similar to the results reported by Tent et al [27]. Ter Wee et al [28] reported on 20 adult donors pre-and 41 days post-donation; GFR and eRPF increased by 65 and 69 % while the FF had decreased significantly from 0.251 to 0.238.…”
Section: Discussionsupporting
confidence: 83%
“…Bugge et al studied eight donors over the immediate 24 h post-nephrectomy [25]; GFR and eRPF increased by 70 % within 1 h and was maintained over 24 h. Pabico et al reported mean post-nephrectomy GFR increase of 37 % and mean eRPF of 55 %; the FF was not significantly different pre-and post-nephrectomy [26], similar to the results reported by Tent et al [27]. Ter Wee et al [28] reported on 20 adult donors pre-and 41 days post-donation; GFR and eRPF increased by 65 and 69 % while the FF had decreased significantly from 0.251 to 0.238.…”
Section: Discussionsupporting
confidence: 83%
“…Short-term studies have shown that selected white donors with hypertension well controlled by a single drug at the time of donation do not have increased risks (52,53). With respect to diabetes, Ibrahim et al reported on 154 donors who developed type 2 diabetes (T2DM) a mean 6 SD of 17.769 years after donation (54).…”
Section: Kidney Donors Are Not Protected From Riskmentioning
confidence: 99%
“…13 Studies that have focused on the outcome of donors with preexisting hypertension have been small; a Dutch study that followed 29 and 13 donors with preexisting hypertension to 1 and 5 years postdonation, respectively, found no difference in postdonation BP or GFR compared with normotensive controls. 14 Textor et al 15 reported no difference in GFR between 24 living donors with preexisting hypertension and normotensive controls followed in the first 1 year postdonation, and BP remained easy to control in the hypertensive group postdonation. 15 In a recent study, 14 Japanese living donors with hypertension and high-normal albumin-tocreatinine ratios (15-30 mg/g) had similar outcomes to normotensive donors in terms of kidney function over 2 years of follow-up.…”
mentioning
confidence: 99%